THE EFFECTS OF MTAD AS ENDODONTIC IRIGANT IN PORPOSE OF INTRAORAL REHABILITATION- a literature review- - Liana Aminov; Mihaela Salceanu; Yllka Decolii; Cristina Antohi; Antonela Beldiman; Laura Elisabeta Checherita (Romanian Journal of Medical and Dental Education, 2019)
Root canal instrumentation is an extremely important, often time-consuming stage of endodontic treatment. This should be regarded as a means of facilitating the penetration of irrigation solutions in all the confines of the canal space, in order to efficiently clean and disinfect it. Of the irrigation solutions available for endodontic use and studied over time, none met the ideal requirements, each with its own advantages and disadvantages. A relatively new irrigant consisting of doxycycline (an antibiotic), citric acid (dentin demineralization) and tween 80 (for detergent action) in aqueous solution, called (Biopure) MTAD, was introduced in 2003 by Torabinejad for endodontic applications. Our study aimed to synthesize the most important properties of this irrigation solution, used alone or in combination with other substances, for the purpose of a more efficient mechanical debridement, followed by a subsequent direct or prosthetic restoration. The methods and systems used for the irrigation or the root canal preparation was not included in the analysis. A search of the literature with works in English published on PubMed and other sites, was conducted until 2019